Analysis of Some Plant Extracts‘ Repellency and Land Use Impacts on Termites - Bäcker, Vital; Gençer, Nimet Sema (Discoveries in Agriculture and Food Sciences, 2024)
It is known that insects have lived on Earth since about 500 million years ago. Humans, on the other hand, have started to be harmful to the ecosystem since they started living on earth only 200,000 years ago. The damage caused by humans to the environment is incomparable with the damage caused by other animals. Until the early 1900s, agricultural activities were mostly done organically. Along with the general industrialization, farmers began to industrialize agriculture. The most dangerous advances were in the production of pesticides and mineral fertilizers, because their effects on plant physiology and the biotope were crucial. Insects are among the most affected in the biotope because since the development of pesticides the planet has lost 70% of the world's insect population. Termites have been one of the species most damaged by insecticide applications. Although conventional pesticides fail to control termites, it seems that such pesticides continue to be used all the time. In addition, the side effects of pesticides in the soil are a great ecology harm. In our research, natural plant extracts, one of the environmentally friendly solutions, were used to control (repel) termites. Plant extracts from three plants (Lantana camara, Tephrosia vogelii and Euphorbia tirucalli) were tested as termite repellents. After crushing fresh leaves, they were soaked in water for 24, 48 and 72 hours. Three doses, 1:9, 2:8 and 3:7 (pounded plants: water), of these extracts were applied to the plots around the active termite mounds. The number of days it took for termites to colonize the treated parcels (repellent effect) was evaluated. The results obtained showed that the soaking time of the plant extracts does not make a significant difference. However, doses and plant variety showed significant differences compared to control plots. The highest repellent effect was determined as 31.3(±1) and 31(±1) days at 3:7 doses of E. tirucalli soaked in water for 72 hours and T. vogelii soaked in water for 48 hours, respectively. However, 1:9 dose of E. tirucalli soaked in water for 72 hours has a lower (13(±1) days) repellent effect. Land use analysis, on the other hand, shows that agricultural and residential areas are installed into termite biotopes. Pastures, crop fields and settlements are the main three land uses found in Kinyinya (east of Burundi). Settlements and crop fields are expanding exponiently. Pastures are the last relatively stable termite biotopes and are gradually transformed in settlements or crop fields. However, considering the effects of termites on the soil, they have great potential to be used as a support to farmers in recycling organic matter. For this reason, it turns out that it is important to use environmentally friendly plant extracts for the protection of termites.